2016
DOI: 10.1111/jbi.12817
|View full text |Cite
|
Sign up to set email alerts
|

The effect of elevation and time on mountain spider diversity: a view of two aspects in the Cederberg mountains of South Africa

Abstract: Aim Our aim is to test if long-term patterns in a alpha and b beta diversity along an elevational transect on two aspects of a mountain are consistent through time using spiders as model organisms, quantify the role of elevation and time (seasonal and inter-annual) in explaining these patterns and partition the relative contribution of nestedness, species turnover and species loss in explaining these diversity patterns.Location The transect is across the Cederberg mountains in the Cape Floristic Kingdom, Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Any more general conclusions are impeded yet because any comparably comprehensive datasets from the tropics are lacking. However, two studies of seasonal shifts of arthropod diversity on subtropical mountains in southern Africa are consistent with our results; an upward shift of diversity peaks was unveiled in a multiple‐year study of ants (Bishop et al, ), as well as in a study of spiders (Foord & Dippenaar‐Schoeman, ). In the latter, a different pattern of the spider diversity shift was detected among the two studied slopes with different precipitation regimes (Foord & Dippenaar‐Schoeman, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Any more general conclusions are impeded yet because any comparably comprehensive datasets from the tropics are lacking. However, two studies of seasonal shifts of arthropod diversity on subtropical mountains in southern Africa are consistent with our results; an upward shift of diversity peaks was unveiled in a multiple‐year study of ants (Bishop et al, ), as well as in a study of spiders (Foord & Dippenaar‐Schoeman, ). In the latter, a different pattern of the spider diversity shift was detected among the two studied slopes with different precipitation regimes (Foord & Dippenaar‐Schoeman, ).…”
Section: Discussionsupporting
confidence: 91%
“…However, two studies of seasonal shifts of arthropod diversity on subtropical mountains in southern Africa are consistent with our results; an upward shift of diversity peaks was unveiled in a multiple‐year study of ants (Bishop et al, ), as well as in a study of spiders (Foord & Dippenaar‐Schoeman, ). In the latter, a different pattern of the spider diversity shift was detected among the two studied slopes with different precipitation regimes (Foord & Dippenaar‐Schoeman, ). Additionally, Meyer et al () revealed seasonal differences in ground‐dwelling arthropod communities along an elevational gradient in the subtropical southwestern US but did not further dissect their patterns or drivers.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the interplay between local climatic conditions (mainly temperature) and evolutionary conserved preferences of species (Wiens & Graham, 2005;Merckx et al, 2015) seem to explain current seasonal and altitudinal gradients, as well as contributing to an understanding of the relative occurrence of Aphodiinae and Scarabaeinae (Lobo, 1997). However, the general bimodal pattern was not only recorded when the seasonal responses of the different groups were analysed separately, but also when the specifi c seasonal pattern at each locality was examined as is recorded in other studies (Jay-Robert et al, 2008;Foord & Dippenaar-Schoeman, 2016).This indicates that these altitudinal patterns are deeply affected by the interplay between the climatic factors infl uencing all insect development stages and the thermal and hydric preferences of species. These results may also indicate that the most stressful periods impose a severe environmental constraint on those species unable to maintain viable populations throughout the entire year at a site because the favourable period shortens with increasing altitude.…”
Section: Discussionmentioning
confidence: 60%
“…Temporal patterns of abundance and diversity that reflect changing seasonal climatic conditions are frequently ignored in tropical rainforests 13 . Patterns of seasonality among invertebrates in particular are poorly understood, with a few notable exceptions 11 , 12 , 14 – 20 . Wolda 15 used a 14 year dataset of light-trapped insects in Panama to demonstrate that populations of insects change both within and between years.…”
Section: Introductionmentioning
confidence: 99%